Efektivitas Kepala KUA dalam Meningkatkan Kinerja Pegawai Ditinjau dari Peraturan Menteri Agama - Iqlima Aghni Nurul Fajri (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Good leaders will have a positive impact on their employees because with good leadership employees will discipline work and concentrate on completing their work. Prior to the leadership of the current head of KUA, it was found that several employees had a lack of responsibility towards tasks, lack of understanding of tasks, and were technology stutterers, but after the current leadership period, employees had a great increased sense of responsibility, therefore researchers are interested in examining how the effectiveness of heads of KUA in improving employee performance. The purpose of this study was to determine the effectiveness of the head of the KUA Kec. Sukasari in improving employee performance and the suitability of the performance of the head of the KUA Kec. Sukasari with the Regulation of the Minister of Religion of the Republic of Indonesia Number 34 of 2016. By using a qualitative descriptive research method, this research was conducted direct observation by means of the field research. And it can be concluded that: Performance of the Head of KUA Kec. Sukasari can be said to be effective in improving the performance of its employees and is in accordance with the Regulation of the Minister of Religion of the Republic of Indonesia No.34 of 2016. Being a good and effective leader will lead us to success. Abstrak. Pemimpin yang baik akan berdampak positif terhadap pegawainya karena dengan kepemimpinan yang baik pegawai akan disiplin kerja dan berkonsentrasi dalam menuntaskan tugasnya. Pegawai KUA Kecamatan Sukasari saat sebelum kepemimpinan kepala KUA yang sekarang, ditemukan sebagian pegawai yang memiliki rasa tanggung jawab kurang terhadap tugas, pemahaman tugas yang kurang, dan gagap teknologi. Namun, setelah masa kepemimpinan yang sekarang pegawai mempunyai peningkatan rasa tanggung jawab yang besar, oleh sebab itu peneliti tertarik untuk meneliti bagaimana efektivitas kepala KUA dalam meningkatkan kinerja pegawai. Tujuan dilakukannya penelitian ini adalah untuk mengetahui keefektivan kepala KUA Kec.Sukasari dalam meningkatkan kinerja pegawai dan kesesuaian kinerja kepala KUA Kec.Sukasari dengan Peraturan Menteri Agama RI Nomor 34 Tahun 2016. Dengan menggunakan metode penelitian deskriptif kualitatif, penelitian ini dilakukan pengamatan langsung dengan cara field research. Dan dapat disimpulkan bahwa: Kinerja Kepala KUA Kec. Sukasari dapat dikatakan efektif dalam meningkatkan kinerja pegawainya dan sudah sesuai dengan Peraturan Menteri Agama RI No.34 Tahun 2016. Dengan menjadi pemimpin yang baik dan efektif akan membawa kita pada keberhasilan.